Assessment of Quality-of-Life in Cancer Patients at Tertiary Care Hospital in North India - Sharma, Bintoo; Tyagi, Harsh; Kumar, Ranjeet; Sharma, Amit (Journal of Coloproctology, 2023)
Introduction Cancer is a disease that emerges as a result of abnormal cell proliferation and their propensity to spread from one bodily region to another. There are over a hundred different types of cancer that impact individuals all over the world. It is difficult to identify in the early stages, but there are certain warning signals that the cells will turn malignant. Quality of life (QOL) is described by the World Health Organisation as “individuals' perception of life, values, objectives, standards, and interests within the cultural framework of the social environment in which they live and in relation to their goals, expectations, standards, and concerns.” QOL assessment in health system is a multidimensional construct that can be measured by evaluating objective levels of health status filtered by the subjective perceptions and expectations of the individual.Aim and Objective To assess socio-demographic factors and quality of life among cancer patients in tertiary care hospital.Materials and Methods A hospital-based prospective observational study was conducted at Guru Gobind Singh Medical College and Hospital Faridkot district, Punjab (India). The study was conducted for a period of six months after getting approval from Institutional Ethical Committee (IEC). Generic instrument, SF-36 was used to assess the QOL. The study was analyzed on SPSS version 26.0 software. Descriptive and analytical analysis was used to describe the results.Results Linear regression was conducted to see the relationship of physical functioning score with age and weight of the patients. The descriptive statistics shows the mean and standard deviation of the variable. The mean of physical functioning score was found to be (M = 27.82, SD = 15.635). The physical functioning score and age, weight of the patients in linear regression shows that the age and weight explain 17.5%Conclusion Treatment revealed that severe and moderate activities restricted nearly half of the assessed patients, with body pain interfering with employment and routine activities. According to the findings of the current study, QOL deteriorates as the disease progresses. Cancer unquestionably has a detrimental influence on patients' quality of life, which is connected to the illness process itself, the therapy administered, and the length of the disease.
Keywords: quality of life; sociodemographic; neurons; cancer; BMF